Social, Educational and Medical Aspects after Cataract Surgery of Bilaterally Blind Children in Kinshasa-Perception of Parents and Children - Stefanie Frech; Adrian Hopkins; Astrid Moanda; Janvier Kilangalanga; Rudolf F. Guthoff (MDPI AG, 2022)
The study investigated the influence of bilateral cataract surgery on the social and educational development of previously bilaterally blind children in Sub-Saharan Africa (SSA), where the prevalence of blindness due to cataract is higher than in high-income countries. The views of both, parents and children, were evaluated with structured interviews based on a newly developed questionnaire related to surgery, follow-up, and family life after surgery. The mean age of the children at interview was 14.4 ± 8.1 years, with 27 females and 26 males. Satisfaction with the outcome of the surgery was reported by 91% of parents. Parents would recommend surgery, because of the children being happy and able to act more independently, with personal, educational and familial factors essentially contributing to the reported satisfaction. The results also showed that 85.0% of children did not wear eyeglasses. Reasons given were mainly cost-related, but also included limited communication between families and health institutions. Providing and maintaining a high-quality and accessible pediatric cataract surgery and healthcare service for follow-up is a major requisite to reduce childhood blindness in SSA. Our study proved the necessity and effectiveness of a community-based rehabilitation program that cares about each individual child, whatever his or her social background.